Pemahaman Mursyid Tarekat Naqsyabandiyah Bustanul Muwahhidin Kecamatan Mandau Terhadap Hadis Suluk - Wahyu, Muhammad Adrika; Andy.N, Nofri (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
This article discusses the implementation of mysticism carried out by Halaqah Thariqat Naqsyabandiyah Bustanul Muwahiddin, Mandau District. The method used is living hadith by revealing the views of the murshid and caliph on related hadiths. The results of this study indicate that the implementation of mysticism carried out by halaqah tariqat naqsyabandiyah Bustanul Muwahiddin Mandau District uses hadith as its foundation. because it uses hadith as a basis for practicing mysticism and the hadiths used do not have the status of maudhu hadith' and the Mursyid's understanding of the relationship between hadith and mysticism practice is about sincere of worship, the suluk performed by the halaqah tariqat naqsyabandiyah Bustanul Muwahiddin Mandau District can be classified as living hadith.